Hierarchical metal–semiconductor–graphene ternary heteronanostructures for plasmon-enhanced wide-range visible-light photocatalysis. Issue 26 (17th June 2019) - Jung, Hayoon; Song, Jaeeun; Lee, Seunghoon; Lee, Young Wook; Wi, Dae Han; Goo, Bon Seung; Han, Sang Woo
Abstract : A high-performance wide-range visible-light photocatalysis platform was constructed from the intimate coupling of morphology-controlled plasmonic metal nanocrystals, a semiconductor, and graphene in a controlled manner. Abstract : Design of heteronanostructures with controlled topologies and configurations is receiving ever-increasing attention for developing practical photocatalytic and photoelectrochemical systems. Herein, we present a promising solar energy conversion platform constructed using the intimate contact of a plasmonic metal (octahedral Au nanocrystals), semiconductor (TiO2 ), and graphene with a well-defined configuration. The shell engineering of Au nanocrystals with TiO2 and graphene through sequential sol–gel, self-assembly, and post-calcination processes could allow the generation of graphene-encapsulated (octahedral Au nanocrystals)@(anatase TiO2 ) core–shell nanostructures. The prepared ternary heteronanostructures exhibited superior photocatalytic hydrogen evolution activity over their binary counterparts, single-component catalysts, and physical mixtures of the constituents under visible-light irradiation ( λ > 400 nm). Furthermore, they effectively utilized the red-light region for photocatalytic reactions. Detailed mechanism studies on the photocatalysis revealed that the prominent photocatalytic performance of the heteronanostructures can be attributed to the transfer of plasmon-induced hot electrons from Au nanocrystals to TiO2 and the subsequent migration of the photogenerated electrons to graphene, which could be facilitated by the intimate contact between the constituent materials. This study can provide a new insight into devising heteronanostructures for efficient light harvesting.